2021
DOI: 10.1097/prs.0000000000008362
|View full text |Cite|
|
Sign up to set email alerts
|

The Goldilocks Procedure with and without Implant-Based Immediate Breast Reconstruction in Obese Patients: The Mayo Clinic Experience

Abstract: he rapidly expanding obesogenic environment, culprit of the current obesity pandemic, has considerably increased the number of obese patients, particularly "morbid" (body mass index greater than or equal to 40 kg/m 2 ) and "super" obese (body mass index ≥50 kg/m 2 ), Background: Obesity is a risk factor for complications in breast reconstruction. Thus, implant-based immediate breast reconstruction in obese women may be controversial. The authors analyzed obese patients who underwent skinsparing mastectomy usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…The authors showed the application of the Goldilocks technique can have a complication rate as high as 18% in high-risk patients. These complication rates are higher than those reported by Chaudhry et al 4 and Bustos et al 5 in obese patients. The authors attribute it to the higher prevalence of diabetes and higher body mass index, which may be contributing factors; however, the univariate and multivariate analyses did not yield any significant associations between clinical comorbidities and risk of developing complications after the initial procedure.…”
contrasting
confidence: 55%
“…The authors showed the application of the Goldilocks technique can have a complication rate as high as 18% in high-risk patients. These complication rates are higher than those reported by Chaudhry et al 4 and Bustos et al 5 in obese patients. The authors attribute it to the higher prevalence of diabetes and higher body mass index, which may be contributing factors; however, the univariate and multivariate analyses did not yield any significant associations between clinical comorbidities and risk of developing complications after the initial procedure.…”
contrasting
confidence: 55%
“…The largest and most recent report published in 2021 by Bustos et al compared cohorts of patients who underwent Goldilocks-only versus Goldilocks with direct implant placement among 105 patients and identified higher rates of complications with direct implant placement. 10 Another report written in 2019 by Chaudhry et al demonstrated an overall complication rate of 9.38% among a cohort of 53 patients with average BMI of 33, including seroma, hematoma, cellulitis, wound dehiscence, and reoperation. 7 In the original description of the Goldilocks technique in 50 breasts (32 patients) with average BMI of 30 by Richardson and Ma in 2012, the most frequent complications were cellulitis (three of 50), seroma (one of 50), and fat necrosis (one of 50).…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of cases describing patients who have ptotic breasts and desire NAC preservation with implantbased reconstruction, but are not candidates for staged reoperation. Since its original report, the Goldilocks technique has been modified and adapted in several ways, to include use of implant-based reconstruction, NAC viability or free nipple grafts, and the addition of ADM (7)(8)(9). This case report presents the detailed technique of using an inferior adipodermal flap in immediate pre-pectoral implant-based reconstruction to achieve an aesthetically pleasing and safe outcome in patients with ptotic breasts who desire NAC preservation.…”
Section: Discussionmentioning
confidence: 99%